Analisis Kesalahan Siswa Terhadap Soal Cerita SPLDV dengan Langkah Penyelesaian Polya Kelas VIII di SMP Plus Darul Hikmah - Mita Akbar Sukmarini; Indah Alfiatul Hasanah (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2022)
This study aims to describe the types of mistakes of grade VIII students of SMP Plus Darul Hikmah Gambiran in solving SPLDV story questions based on Polya's procedures. The Polya procedure is a diagnostic method for identifying the error category of an answer from an essay test. This research is a qualitative research. Data collection was carried out using observation and interview methods. The research subjects were taken 6 of the 17 students of class VIII, each consisting of 2 students from the upper, middle, and lower classes. The classification is based on ranking the observations of students. The data validity test was done by using triangulation technique. The results of the analysis of the types of errors of the VIII grade students of SMP Plus Darul Hikmah in solving math story questions about SPLDV material based on Polya's procedures can be concluded that the error in understanding the problem, the cause is that the research subject does not understand the SPLDV material besides lack of practice in solving various SPLDV questions. Errors in planning, the cause is because the average person is not able to make a mathematical model that is in accordance with the sentence of the story in the problem and the lack of understanding of the research subject regarding the prerequisite material about number operations. Mistakes in implementing the plan, the cause is lack of mastering basic mathematical operations, namely addition, subtraction, multiplication and division and haste. Error checking, the cause is the previous error and the lack of thoroughness of the research subject.